The Linear Structural Relationship of Research - Supported E ff ificiency Factors in Secondary Educational Service Area 7 - Changkep, Mr.Kriangkrai (วารสารวิชาการ มหาวิทยาลัยราชภัฏพระนคร, 2017)
The purpose of this research is to study the Research-supported efficiency factors in SECONDARY EDUCATIONAL SERVICE AREA 7. The population in this research is supervisors and teachers with research in SECONDARY EDUCATIONAL SERVICE AREA 7. The fiscal year is 2015. The total number of people is 1171 guy. The sample used in this study is supervisors and teachers with research in SECONDARY EDUCATIONAL SERVICE AREA 7. The fiscal year is 2015. The total number of sample is 313 guy. The independent variable in this study is agencies factor, personal factor, process management factor and Other factors. The dependent variable in this study is research efficiency. Tools used in research is multiple choice questionnaire (Rating Scale) data analysis using the average ( ), Standard deviation (S.D.) and Statistics and data analysis of respondents and test hypotheses in article 1. The analysis Confirmatory Factor Analysis (CFA) test hypotheses in article 2. Analysis using the Pearson correlation (Pearson’ s product moment correlation). Statistical analysis with LISREL. The results of research: The factors that support research and four factors of research at a high level. The quality and benefits of research can affect the performance of research on a large scale. The results of confirmatory factor analysis (CFA) of independent variable have 4 factors is 1) agencies factor 2) personal factor 3) process management factor 4) Other factors. And the results of confirmatory factor analysis (CFA) of dependent variable have 2 factors is 1) The benefits of research. 2) The quality of research. The analysis of the linear structural relationship of research-supported efficiency factors in SECONDARY EDUCATIONAL SERVICE AREA 7 is Every factor correlated structure.